WSN clustering routing algorithm based on Cuckoo Search algorithm optimized K-means - Kailei ZHU; Aijing SUN (物联网学报)
In order to extend the lifetime of wireless sensor network (WSN), a clustering routing algorithm for WSN based on Cuckoo Search (CS) algorithm optimized K-means was presented.In the clustering stage, the initial cluster centers were selected by CS algorithm, which make the clustering results of the K-means algorithm more uniform to balance node energy consumption.The remaining energy of the node, the distance from the center of the cluster were comprehensively considered in the cluster election, and the weight according to the remaining energy of the node was dynamically adjusted.In the data communication stage, in order to further balance the load of the cluster head, the remaining energy of the relay node and its load, and the cluster head routing energy consumption were comprehensively considered, CS algorithm was combined to plan routing for the cluster head.The simulation results show that the proposed algorithm is better than LEACH-K, LEACH-improve and DTK-means in terms of energy consumption balance.With the death of the first node as the life cycle of the network, the network lifespan was increased by 173%, 21%, and 6% respectively.The proposed algorithm effectively extending the network life cycle.